Polymers Blending as Release Modulating Tool in Drug Delivery - Ghasemiyeh, Parisa; Mohammadi-Samani, Soliman (Frontiers in Materials, 2021)
Different polymeric materials have been used as drug delivery vehicles for decades. Natural, semisynthetic, and synthetic polymers each one has their own specific characteristic and due to the physicochemical limitations of each polymer tuning the release rate and targeting the active ingredient to a specific organ or site of action is a complicated task for pharmaceutical scientists. In this regard using polymer blends has been considered as an attractive method in which the physical and/or chemical characteristics of different polymers are modified in order to fabricate a novel and unique drug delivery system. There is three major polymers blend that are used for drug delivery purposes including physical mixtures, core-shell model, and block copolymer model. Each of these types of polymer blends could significantly affect the loading capacities and the kinetics of drug release from the relevant formulations. By using appropriate copolymer or polymer blends tuning the release profile would be dependent on the temperature and pH of the environment, and physiochemical properties of the target organs. Also, possible molecular interactions among polymers and drug molecules should be considered. In this review, first of all, the purpose of polymer blending in drug delivery systems has been discussed. Then, different methods of polymer blending have been summarized. Finally, the consequence of each blending method on drug release profile and kinetics of drug release have been discussed.